Developing Islamic Education and Character Based Learning Models Based on Emotional Intelligence to Improve Morality of Students at Budi Utomo Vocational School (SMK)Way Jepara - Anik Anik Sudarmi; Muhammad Yusuf (Journal of Research in Islamic Education, 2022)
According to government regulations, PAI and Behavior Based subjects in SMK are given the task of producing students who are pious and have noble character. However, in practice, learning PAI and Behavior Based at SMK Budi Utomo Way Jepara tends to focus on increasing knowledge. This condition is exacerbated by the presence of some students who practice despicable morals. Therefore, a PAI and Budi Pekerti learning model is needed which is oriented to the development of students' morals. The PAI and Behavior Based learning model based on emotional intelligence is seen as a solution, because this intelligence leads to moral development. The learning model is assessed from the aspects of validity, practicality and effectiveness. To achieve this goal, the Plomp model development research was used, which consisted of five phases, namely: 1) initial investigation, 2) design, 3) realization/construction. 4) test, evaluation and revision, and 5) implementation. The trial was carried out using a pretest-posttest pre-experimental design in eight classes of class XI students in the odd semester of 2021/2022. Data collected through interviews, observations, questionnaires / questionnaires, reflection sheets and action plans were analyzed using descriptive analysis, Kolmogorov-Smirnov and paired T-test. The results showed that 1) the learning model got a very valid score with an average value of 94.53 which means it is very valid, can be used without revision 2) the learning model is considered very practical with an average value of 95.83 which means it is very practical, can be used without revision, and 3) the learning model is considered very good and can improve morals. Thus the learning model can be used to foster the morals of students at Budi Utomo Way Jepara Vocational School, as well as an effective learning model or able to improve students' morals (attitudes) towards Respect and Obedience to Parents and Teachers.